COVID-19 and the digestive system: A comprehensive review - Wang, Ming-Ke (World J Clin Cases, 2021)
The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) is spreading at an alarming rate, and it has created an unprecedented health emergency threatening tens of millions of people worldwide. Previous studies have indicated that SARS-CoV-2 ribonucleic acid could be detected in the feces of patients even after smear-negative respiratory samples. However, demonstration of confirmed fecal-oral transmission has been difficult. Clinical studies have shown an incidence rate of gastrointestinal (GI) symptoms ranging from 2% to 79.1% in patients with COVID-19. They may precede or accompany respiratory symptoms. The most common GI symptoms included nausea, diarrhea, and abdominal pain. In addition, some patients also had liver injury, pancreatic damage, and even acute mesenteric ischemia/thrombosis. Although the incidence rates reported in different centers were quite different, the digestive system was the clinical component of the COVID-19 section. Studies have shown that angiotensin-converting enzyme 2, the receptor of SARS-CoV-2, was not only expressed in the lungs, but also in the upper esophagus, small intestine, liver, and colon. The possible mechanism of GI symptoms in COVID-19 patients may include direct viral invasion into target cells, dysregulation of angiotensin-converting enzyme 2, immune-mediated tissue injury, and gut dysbiosis caused by microbiota. Additionally, numerous experiences, guidelines, recommendations, and position statements were published or released by different organizations and societies worldwide to optimize the management practice of outpatients, inpatients, and endoscopy in the era of COVID-19. In this review, based on our previous work and relevant literature, we mainly discuss potential fecal-oral transmission, GI manifestations, abdominal imaging findings, relevant pathophysiological mechanisms, and infection control and prevention measures in the time of COVID-19.